2022
DOI: 10.21883/pss.2022.04.53500.262
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure formation in quartz single crystal at the early stages of deformation

Abstract: Accumulation of defects in the synthetic quartz single crystal has been investigated at the early stages of deformation. Process is studied with the help of three independent nondestructive techniques, namely: acoustic emission, X-ray computed tomography and synchrotron radiation topography. It is shown that results obtained by the three techniques are consistent with each other, allow detecting the area of defect formation and, what is more important, to match acoustic emission parameters with the ones of def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Detailed studies of the defective structure, conducted using X-ray computed tomography and X-ray diffraction imaging (XDI) [11], showed that even at low loads in a sample of a single crystal of quartz, microcracks are formed, which are the sources of acoustic emission signals.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies of the defective structure, conducted using X-ray computed tomography and X-ray diffraction imaging (XDI) [11], showed that even at low loads in a sample of a single crystal of quartz, microcracks are formed, which are the sources of acoustic emission signals.…”
Section: Resultsmentioning
confidence: 99%
“…Within the framework of modern concepts of mechanics and strength physics, the destruction of materials under external energy influences is a spatio-temporal process caused by the formation and development of defects at various structural (scale) levels. Quite close attention is paid to this problem and a lot of experimental and analytical studies have been devoted, some of which reflect the works [1][2][3][4][5]. The patterns of this process are largely determined by the structure of materials, which is characterized by the shape and size of grains, porosity, the presence of microdefects, and along with the chemical composition determines the physical properties of materials, including strength.…”
Section: Introductionmentioning
confidence: 99%
“…Cracks in metals, polymers and crystals have been studied by now with a large number of methods: fractoluminescence (FL), electron microscopy, acoustic emission, X-ray microtomography, etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. It is found that the crystal fracture process begins with the accumulation and consolidation of the smallest " primary" cracks with sizes of a few nm [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…They are formed when dislocations break through barriers that prevent them from moving along sliding planes [6][7][8][9]16]. It is found that in a stressed solid, cracks first accumulate independently of each other throughout the volume, and then they merge [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], enlarge and form a fracture centrea main crack. All of these processes start with the formation of " primary" cracks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation